PENGARUH KONTROL DIRI TERHADAP KECENDERUNGAN PERILAKU CYBERSLACKING MAHASISWA UNIVERSITAS HKBP NOMMENSEN - Lisna Simbolon; Asina Christina Rosito (Universitas HKBP Nommensen, 2021)
This study aims to determine whether there is an effect of self-control on the tendency of cyberslacking behavior in students of Universitas HKBP Nommensen. The sample were 263 students from various departments. The data collection method used psychological scale, namely the self-control scale and the cyberslacking scale. Data analysis technique to test the hypothesis is simple linear regression. From the results of the regression test, the results show that there is a significant negative effect of self-control on cyberslacking. The contribution of self-control to cyberslacking is 15% which indicates that self-control has an effect of 15% on cyberslacking behavior in college students.